Impact of Surface Properties of Granular Activated Carbon and Preozonation on Adsorption and Desorption of Natural Organic Matter - BAKIRCI, KOZET; CAN, ZEHRA SEMRA (MARY ANN LIEBERT INC, 2009)
Laboratory studies were performed with the surface water taken from the Omerli Reservoir in Istanbul. Adsorption and desorption of natural organic matter (NOM) were studied with four granular activated carbon (GAC) samples having different surface properties. Ozonation at optimum dose, biological treatment, and their combination were also applied to raw water to examine the effect of each treatment on adsorption and desorption onto GAC. Different ozone dosages were applied in the range of 0.5-3 mg O(3)/ mg dissolved organic carbon (DOC) in order to find the optimum ozone dose that maximizes the biodegradable dissolved organic carbon (BDOC) formation. BDOC formation is targeted in systems where biologic degradation takes place such as in biologic activated carbon columns. Ozonation was found to increase the formation of BDOC up to an applied dose of 2 mg O3/ DOC. Among the GAC, the chemically activated carbon, CAgran, exhibited the best desorption but worst adsorption compared with the steam activated carbons. GAC types with higher pH(PZC) (Norit 1240 and Row Supra) exhibited the largest NOM adsorption capacity for all water types tested. In this study, the surface chemistry was more influential on adsorption than pore structure.
Keywords: natural organic matter; granular activated carbon; adsorption; desorption; biodegradable dissolved organic carbon; ozonation; HUMIC SUBSTANCES; WATER-TREATMENT; BIOLOGICAL FILTRATION; OZONE; OZONATION; REMOVAL; NOM